Modulational Stability Analysis of Ion Temperature Gradient Modein Electron-ion Plasma - Aziz Khan Khan; U. Zakir; Q. Haque; I. Haq; F. Khan (Kuwait Journal of Science)
A theoretical investigation of the modulational stability of the ion temperature gradient (ITG) mode in electron–ion plasma is presented. The technique of reduction perturbation (RPT) is applied to the basic magneto hydrodynamic equations of ITG mode and drive the nonlinear schrodinger equation. Critically, it is noticed that plasma dynamics depend on the coefficients of onlinearity and dissipation of the non-linear schrodinger equation, these coefficient are strongly related with the plasma  ariables. The present model, depicting the modulational stable and unstable region for the ion temperature gradient mode in the electron-ion plasma. The present investigation may be helpful in space and laboratory plasma e.g., fusion confinement devices.